Factors associated with suicidal ideation among medical students during the initial phase of the COVID-19 pandemic in Peru: A multicenter study. Issue 2 (7th February 2023) - Crisol-Deza, Diego; Poma-Ramírez, Diana; Pacherres-López, Andrés; Noriega-Baella, Carlos; Villanueva-Zúñiga, Luis; Salvador-Carrillo, José; Huarcaya-Victoria, Jeff
Abstract: We aimed to describe the prevalence and factors associated with suicidal ideation in a sample of 1238 medical students from different medical schools in Peru based on question 9 of the Patient Health Questionnaire (PHQ-9). Our results revealed that 17.9% of the participants had suicidal ideation. Furthermore, using logistic regression, we found that not practicing any religion, the presence of clinically significant depression, and the presence of clinically significant anxiety were statistically related to the presence of suicidal ideation. Our results indicate that suicidal ideation was highly prevalent in the sample of medical students studied.